PTU-189 Research design implications from a survey and focus group of ibs sufferers at a specialised patient conference. (22nd June 2015) - Etherson, KJ; Mason, JM; Emmett, C; Yiannakou, Y
Abstract : Introduction: A large patient conference attended by >150 patients with irritable bowel syndrome (IBS) was hosted by County Durham and Darlington NHS Foundation Trust in July 2014. The aims were to educate, support and gain patients' perspectives into their condition. A 45-minute session on "engaging with research" described current research and thinking into IBS, and then offered participants the opportunity to complete a survey and focus group discussion on the topic. This session was repeated three times during the conference. Method: Each of the 3 sessions followed a prescribed format. A survey sheet asked participants to complete 5 multiple choice questions on health research in IBS. The cohort were then split into two focus groups led separately by a professor and specialist in health research design (JM) or a research fellow who treats and recruits patients with IBS into clinical studies (KE). Survey data was analysed quantitatively after the conference. Qualitative data was shared between researchers after each session and emerging themes explored further in the subsequent focus groups for validation. Results: 78 people attended and participated over 3 sessions. Response rates varied between survey items. Patients felt that research priorities should be; investigating the causes of IBS (54%), new drug treatments (20%), and developing diagnostic tests (18%). As research participants, 85% felt it was acceptable to keep a bowel diary for ≥4 weeks and 63% felt ≥5 visits in a 6 month period during a clinical trial were acceptable. Motivations to participate in clinical trials were due to; a new treatment for IBS (65%), altruism (37%) and other factors (11%). 68% were willing to participate in studies where they might receive a placebo or sham treatment as part of the study design. Themes emerging from the focus groups emphasised the need to research the causes of IBS, particularly as a diagnosis was felt to validate their experiences and brought a sense of gaining control. The treatment of pain was felt to be "a first priority", as was a wish for a side-effect free "magic pill", but expectations of these were realistic. Most agreed that their IBS symptoms were highly variable and so longer diary exercises were acceptable and required. Conclusion: Methodologists and clinicians involved in the design of clinical trials of investigational medicinal products for IBS should consider our patients' ideas and their acceptability. In particular: lengthening symptom diaries, monitoring pain as a priority symptom, and frequent monthly study visits. Recruitment is not hindered by placebo or sham treatment arm designs and most patients are motivated to participate by receiving a new treatment over altruism or honorariums. Disclosure of interest: None Declared.